2020
DOI: 10.1002/jso.25964
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of lymphatic invasion in the esophageal region in patients with adenocarcinoma of the esophagogastric junction

Abstract: Background and Objectives The lymphatic flow around the esophagogastric junction is complicated. Therefore, it is unclear whether lymphatic invasion in the esophageal region (eLI) and in the gastric region (gLI) in patients with adenocarcinoma of the esophagogastric junction (AEG) equally affect the incidence of lymph node metastases (LNM), and consequently, survival. Methods We retrospectively reviewed clinicopathological data of 175 patients with AEG between January 2008 and July 2017. Risk factors for LNM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…lww.com/SLA/ D666). [4][5][6][7][8] Of note, in 3 studies that reported the treatment landscape in patients with metastatic PDAC in the Netherlands, the percentage of patients with anticancer treatment ranged from 18% to 29%, and the median overall survival times were in the range of 2 months. 5,7,8 These poor survival data are in line with a large SEER database analysis, that reported a median overall survival for metastatic PDAC diagnosed in the US between 1993 and 2013 of 2 months.…”
Section: Comment On: "A Randomized Controlled Trial Evaluating Electr...mentioning
confidence: 99%
See 2 more Smart Citations
“…lww.com/SLA/ D666). [4][5][6][7][8] Of note, in 3 studies that reported the treatment landscape in patients with metastatic PDAC in the Netherlands, the percentage of patients with anticancer treatment ranged from 18% to 29%, and the median overall survival times were in the range of 2 months. 5,7,8 These poor survival data are in line with a large SEER database analysis, that reported a median overall survival for metastatic PDAC diagnosed in the US between 1993 and 2013 of 2 months.…”
Section: Comment On: "A Randomized Controlled Trial Evaluating Electr...mentioning
confidence: 99%
“…[4][5][6][7][8] Of note, in 3 studies that reported the treatment landscape in patients with metastatic PDAC in the Netherlands, the percentage of patients with anticancer treatment ranged from 18% to 29%, and the median overall survival times were in the range of 2 months. 5,7,8 These poor survival data are in line with a large SEER database analysis, that reported a median overall survival for metastatic PDAC diagnosed in the US between 1993 and 2013 of 2 months. 6 As an explanation for not using established and approved medical treatment options for PDAC with (metachronous or synchronous) metastases authors mostly name poor performance status and wish of the patient.…”
Section: Comment On: "A Randomized Controlled Trial Evaluating Electr...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Several previous studies described clinical indicators to predict MLNMs in patients with EGJC. [10][11][12] In addition, it has been a controversial issue whether MLN dissection has survival bene ts. [5][6][7][8] The present study was conducted to identify the factors associated with mediastinal lymph node positivity in patients with proximal gastric tumors who received curative surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several previous studies described clinical indicators to predict MLNMs in patients with EGJC. [10][11][12] In addition, it has been a controversial issue whether MLN dissection has survival bene ts. [5][6][7][8] The present study was conducted to identify the factors associated with mediastinal lymph node positivity in patients with proximal gastric tumors who received curative surgical treatment.…”
Section: Introductionmentioning
confidence: 99%